Odpowiedzi

2009-12-01T17:46:26+01:00
A)

2x - 1,1 y = 0,7
0,5x + 1,1 y = 4,3

2,5x=5
x=2

2x-1,1y=0,7
4-1,1=0,7

-1,1y=-3,3
y=1

b)

x - 2y = 4
- x + 3 y = 0

y=4

x-2y=4
x-8=4

x=12
2009-12-01T17:51:42+01:00
A)
2x - 1,1 y = 0,7
0,5x + 1,1 y = 4,3

2,5x=5/:2,5
x=2

2x - 1,1 y = 0,7
x=2

2*2-1,1y=0,7
x=2

4-1,1y=0,7
x=2

-1,1y=0,7-4
x=2

-1,1y=-3,3/:(-1,1)
x=2

y=3
x=2

b)
x - 2y = 4
- x + 3 y = o

y=4
x - 2y = 4

x-2*4=4
y=4

x-8=4
y=4

x=4+8
y=4

x=12
y=4


2009-12-01T17:55:27+01:00
Przykład A
2x-1,1y =0,7
0,5x+1,1y =4,3
2,5x=5/2,5
x=2
2x-1,1y=0,7
4-1,1=0,7
-1,1y=-3,3 /-1,1
y=1

Przykład B
x-2y =4
-x+3y=0
y=4
x-2y=4
x-8=4
x=12